Diagnosis and Treatment of Conn Syndrome: A Case Study - Abdaly, Muhammad Syah; Juliyanti, Juliyanti; Marbun, Maruhum Bonar (UI Scholars Hub, 2017)
Acute neuromuscular disorder is a commonly found medical condition, which may prove to be fatal in certain conditions. Hypokalemia is one possible cause of neuromuscular disorder. In patient with hypokalemia accompanied with hypertension, primary hyperaldosteronism might be the primary cause. Primary hyperaldosteronism (Conn syndrome) is clinically known as a triad, which is consists of hypertension, hypokalemia, and metabolic alkalosis. In this article, the case of a patient with neuromuscular disorder is presented, and after evaluation, it was found that the patient was suffered from the Conn syndrome